2000
DOI: 10.1053/jhep.2000.8539
|View full text |Cite
|
Sign up to set email alerts
|

Rifamycin SV and rifampicin exhibit differential inhibition of the hepatic rat organic anion transporting polypeptides, Oatp1 and Oatp2

Abstract: The antibiotics, rifamycin SV and rifampicin, are known to interfere with hepatic bile salt and organic anion uptake. The aim of this study was to explore which transport systems are affected. In short-term-cultured rat hepatocytes, low concentrations (10 mol/L) of both compounds inhibited mainly sodium-independent taurocholate uptake, whereas higher concentrations (100 mol/L) also inhibited sodium-dependent taurocholate uptake. In Xenopus laevis oocytes expressing the Na ؉ /taurocholate cotransporting polypep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 31 publications
6
58
0
Order By: Relevance
“…This result is consistent with previous studies in which rifampin has been found to inhibit hepatic uptake in cultured rat hepatocytes 51 and perfused rat liver. 53 However, our results are novel in that they, (1) demonstrate that rifampin blocks uptake by hepatocytes in the intact liver in vivo, (2) demonstrate that rifampin blocks the initial step of uptake into the cytosol and (3) demonstrate that inhibition delivery of bilirubin to the hepatocyte cytosol, where conjugation occurs, this is a surprising result.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This result is consistent with previous studies in which rifampin has been found to inhibit hepatic uptake in cultured rat hepatocytes 51 and perfused rat liver. 53 However, our results are novel in that they, (1) demonstrate that rifampin blocks uptake by hepatocytes in the intact liver in vivo, (2) demonstrate that rifampin blocks the initial step of uptake into the cytosol and (3) demonstrate that inhibition delivery of bilirubin to the hepatocyte cytosol, where conjugation occurs, this is a surprising result.…”
Section: Discussionsupporting
confidence: 94%
“…In order to demonstrate the sensitivity of the liver transport assays, we evaluated transport in rats treated for 4 d with rifampin, an antibiotic used to treat tuberculosis, and a potent inhibitor of rat and human organic anion transporters. [50][51][52][53][54] The time course of fluorescein redistribution over 6 min in rifampintreated and vehicle-treated control rats is shown in Figure 3. The top three panels show that, similar to the results shown in Figure 2, fluorescein rapidly redistributes from the sinusoids into the hepatocyte cytosol and canaliculi in a control rat.…”
Section: Resultsmentioning
confidence: 99%
“…Previous in vitro studies have shown that rifampicin is an inhibitor of Oatp1a4, Oatp1b2, OATP1B1, and OATP1B3 (44)(45)(46). Rifampicin, an antibiotic mainly used in the treatment of tuberculosis, has been shown to reduce the elimination of BSP and to increase serum-conjugated bilirubin and UCB levels (30,47).…”
Section: Figurementioning
confidence: 99%
“…For example, uptake of ICG is inhibited by rifamycin (Paumgartner, 1975), which is a potent liver OATP inhibitor (Fattinger et al, 2000;Vavricka et al, 2002). In contrast, coadministration of erythromycin and gadoxetic acid was recently found to have no effect on liver imaging (Huppertz et al, 2011).…”
Section: Interaction Of Drugs With Transport Systemsmentioning
confidence: 99%